Rotation, combined structure, semi cylindrical weir- gate, energy loss, discharge coefficient. - M. M; A. S; S. Z (مهندسی منابع آب, 2014)
The combined weir- gate is a structure which may replace weir and gate in channels. The semi cylindrical weir- gate has a higher discharge coefficient in comparison with the sharp crested weir- gate because of the curvature on the weir section which the water wedge adheres momentarily. In a weir– gate structure, the rate of the passing flow discharging above the weir and through the gate depends on the structure’s position. In the present research, hydraulics of the semi cylindrical weir- gate rotating the flow around the off-center axis, so that the gate opening height remains constant were investigated. The experiments were conducted in a rectangular and horizontal flume with the length of 5 m and width of 75 mm in the Sari Agricultural Sciences and Natural Resources University Hydraulics laboratory. PVC pipes with 40, 50, 60, 70 and 85 mm diameters were used as semi cylindrical structures. Experimental results illustrate that the maximum and minimum discharge coefficient were observed in the 330 and 90 degree angels, respectively. Furthermore, the maximum and minimum energy loss were observed for the 90 and 180 degree angels. Moreover, the results show that in addition to the angle of the semi cylindrical curvature toward the horizontal line, the structure diameter affected the discharge coefficient and energy loss. In addition, the best relationship for estimating the flow discharge is proposed.